Determination of optimum conditions in preparing highly reactive electrogenerated zinc by gas chromatograph - Abdul Jalil, Aishah; Kurono, Nobuhito; Tokuda, Masao (2004)

(untitled)
Highly reactive electrogenerated zinc metal (EGZn/Naph) was readily prepared by electrolysis of a DMF solution cotaining naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. The reactivity of this EGZn/Naph elucidated by an efficient transformation of ethyl 2-bromolbutanoate as a model substrate into the corresponding organozinc compound, which can not be achieved by the use of usual zinc metal. It was found that the electrolysis at -10C at a constant current of 60 mA/cm2 under nitrogen atmosphere was the optimum conditions in preparing of the EGZn/Naph.